Effects of different pruning patterns on fruit commodity, nutritional quality and yield of cherry tomato - WANG Huiru; YAN Sihua; GAO Yanming; LI Jianshe (浙江大学学报. 农业与生命科学版)
This study aims to research the influence of various pruning patterns to fruit commodity, nutritional quality, growth period and yield of cherry tomato. We selected Solanum lycopersicum cv. ‘Xiangfei3’ as the experimental material, set up five pruning patterns (T1, one-bar; T2, two-bar; T3, three-bar; T4, four-bar; T5, five-bar), investigated its phenotypic traits and growth period, measured its nutritional quality and yield, and used principal component analysis, analysis of variance and other statistical methods for data analysis. The results indicated that the effect of pruning patterns on the commodity of cherry tomato was significant, and the comprehensive score of commodity of five-bar pruning treatment was higher than the other treatments. The content of vitamin C in the five-bar pruning was significantly higher than the other treatments, and the sucrose content increased with different degrees compared with the other treatments. At the same time, the yield of five-bar pruning treatment was the highest (5 789.85 kg/667 m2), which was significantly different from that under the one-bar pruning treatment. It can be seen that five-bar pruning is more conducive to improve fruit commodity, accumulate nutritional quality ingredients and increase yield of cherry tomato.